R&D expenditures as a driver of investment and economic growth in Kazakhstan - Kalkabayeva, G.M.; Kurmanalina, A.K.; Atabayeva, A.K.; Tyan, O.A. (Journal of Economic Research & Business Administration, 2025)
This article examines the impact of R&D expenditures on capital investment and economic growth in Kazakhstan. R&D spending plays a crucial role in the development of new technologies, the improvement of existing products and processes, and stimulates the advancement of science and human capital. Moreover, active R&D financing is often accompanied by investments in fixed capital, including equipment, infrastructure, production facilities, and more, which suggests a potential relationship between the two types of investment. The study aims to assess how R&D expenditures influence capital investment and GDP growth, taking into account potential time-lag effects. Using a VAR framework estimated in first differences, the study focuses on short-term dynamics and predictive relationships among changes in the variables. Stationarity was tested using the Augmented Dickey–Fuller (ADF) test, and temporal predictability was assessed via the Granger causality test. The study takes into account that R&D expenditures may affect capital investment with a certain time lag, as capital investment can be directed toward the implementation of new technologies and innovations, which are the outcomes of R&D activities. The results of the VAR model show that changes in R&D expenditures, although they do not have a statistically significant direct effect on changes in capital investment, have a positive impact on changes in GDP growth rates with a one-period lag. In turn, Granger causality tests confirm a unidirectional causal relationship running from changes in GDP growth rates to changes in R&D expenditures. Overall, the results highlight the complexity and time-lag dependence of the interaction between innovation, investment, and growth in Kazakhstan. Key words: R&D expenditures, capital investment, economic growth, VAR model.